2000
DOI: 10.1099/0022-1317-81-1-243
|View full text |Cite
|
Sign up to set email alerts
|

High genetic diversity, distant phylogenetic relationships and intraspecies recombination events among natural populations of Yam mosaic virus: a contribution to understanding potyvirus evolution

Abstract: To evaluate the genetic diversity and understand the evolution of Yam mosaic virus (YMV), a highly destructive pathogen of yam (Dioscorea sp.), sequencing was carried out of the C-terminal part of the replicase (NIb), the coat protein (CP) and the 3h-untranslated region (3h-UTR) of 27 YMV isolates collected from the three main cultivated species (Dioscorea alata, the complex Dioscorea cayenensis-Dioscorea rotundata and Dioscorea trifida). YMV showed the most variable CP relative to eight other potyviruses. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
83
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 40 publications
10
83
0
3
Order By: Relevance
“…Recombination in natural populations has been reported for other plant viruses (5,10). It has been proposed that recombination can be advantageous for RNA viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Recombination in natural populations has been reported for other plant viruses (5,10). It has been proposed that recombination can be advantageous for RNA viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Spatial separation patterns with very few cells expressing both viruses have been documented for different potyvirus species -PPV, TVMV and Clover yellow vein virus (CIYVV) (Dietrich and Maiss, 2003). However, there is substantial evidence for intra-and interspecific recombination between potyviruses derived from sequencing and phylogenetic analysis of natural virus populations (Bousalem et al, 2000;Cervera et al, 1993;Chare and Holmes, 2006;Desbiez and Lecoq, 2004;Fanigliulo et al, 2005;Ohshima et al, 2002;Tan et al, 2004;Zhong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The recombination potential of TBSV, Turnip mosaic virus (TuMV), Yam mosaic virus (YMV) and BMV has been shown to depend on the host (Bousalem et al, 2000;Desvoyes and Scholthof, 2002;Dzianott and Bujarski, 2004;Ohshima et al, 2002). Screening the recombination efficiency of TBSV using a yeast single-knockout library revealed that host genes involved in RNA degradation were suppressing the generation of new viral RNA recombinants.…”
Section: Discussionmentioning
confidence: 99%
“…RNA recombination is one of the fundamental aspects of the life cycle and evolution of RNA viruses and contributes significantly to a high level of variation in viral RNAs, as demonstrated by sequencing of virus populations (6,7,32,34,45,50,58) and with experimental in vivo systems for animal viruses (19,31,44,51,54), plant viruses (1,2,12,15,25,35,41,53,55,59), bacteriophages (38), and retroviruses (40). In vitro recombination assays (reviewed in reference 21) revealed either a nonreplicative (breakage-religation) (22) or replicative (template switch) (3,28,30,36) mechanism of crossover.…”
mentioning
confidence: 99%